2021
DOI: 10.1371/journal.pone.0247127
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of yellow passion fruit in response to cucumber mosaic virus infection

Abstract: The cultivation and production of passion fruit (Passiflora edulis) are severely affected by viral disease. Yet there have been few studies of the molecular response of passion fruit to virus attack. In the present study, RNA-based transcriptional profiling (RNA-seq) was used to identify the gene expression profiles in yellow passion fruit (Passiflora edulis f. flavicarpa) leaves following inoculation with cucumber mosaic virus (CMV). Six RNA-seq libraries were constructed comprising a total of 42.23 Gb clean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Based on the KEGG pathway and GO enrichment of transcriptome data, Guo et al showed a complex regulatory network for PM resistance in pumpkin that may also involve hormone signal transduction pathways 20 . Chen et al reported that genes associated with plant hormone signal transduction, detoxification, phenylpropanoid biosynthesis, photosynthesis and chlorophyll metabolism were significantly affected by CMV infection in yellow passion fruit 21 . Transcriptome results showed that the moderate resistance of Pinus pinaster to Fusarium circinatum may be explained by the expression profiles pertaining to early recognition of the pathogen, the induction of pathogenesis-related proteins and the activation of complex phytohormone signaling pathways 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on the KEGG pathway and GO enrichment of transcriptome data, Guo et al showed a complex regulatory network for PM resistance in pumpkin that may also involve hormone signal transduction pathways 20 . Chen et al reported that genes associated with plant hormone signal transduction, detoxification, phenylpropanoid biosynthesis, photosynthesis and chlorophyll metabolism were significantly affected by CMV infection in yellow passion fruit 21 . Transcriptome results showed that the moderate resistance of Pinus pinaster to Fusarium circinatum may be explained by the expression profiles pertaining to early recognition of the pathogen, the induction of pathogenesis-related proteins and the activation of complex phytohormone signaling pathways 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, this TF was reported to interact with the nucleocapsid protein of sonchus yellow net virus (SYNV) in N. benthamiana [63]. Through RNA-seq analysis, upregulation of 7 differentially expressed genes (DEGs), including the NAC family transcription factors, was identified in passion fruit (Passiflora edulis) during the infection of CMV [64]. NAC1 TF was discovered through genetic regulation analysis using retrotransposons and suggested to play a critical role in hormonal regulation during groundnut bud necrosis virus (GBNV) and tomato leaf curl New Delhi virus (ToLCNDV) infection [65].…”
Section: Nac Transcription Factors Familymentioning
confidence: 99%
“…(passion fruit) is highly nutritious and possesses an exquisite sweet taste, making it widely cherished by the majority of consumers [ 1 ]. However, with the extensive cultivation of passion fruit in China, diseases have proliferated across all provinces due to the introduction, sale, and propagation of infected seedlings [ 2 ]. Among these diseases, cucumber mosaic virus (CMV) disease stands out as one of the primary viral infections affecting passion fruit plants [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%